ANALISIS KONSENTRASI LOGAM BERAT (Cu, Fe, Zn) KONDUKTIVITAS LISTRIK DAN DENSITAS AIR SUNGAI GAUNG DI DESA SEMAMBU KUNING KECAMATAN GAUNG KABUPATEN INDRAGIRI HILIR - Dahlia Segeryanti; Riad Syech; Usman Malik (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
A research has been done on analysis of concentration of heavy metals (Cu, Fe, Zn) electrical conductivity and density of the Gaung river water. The method that used in this research was an experimental. The samples of Gaung river water in the village of Semambu Kuning was taken three times in each point: the Dusun Terentang, Dusun Sejahtera, and Dusun Mulia. Measurement of the concentration of heavy metals was performed by using Atomic Absorption Spectroscopy(AAS), while the electrical conductivity measurements were performed using conductivitymeter and density was measured by using a hydrometer. The results showed that the concentration of iron(Fe) from each points was 1.28x10-6 kg/l, 1,25x10-6 kg/l, and 1,32x10-6 kg/l, respectively. Concentrations of copper(Cu) oneach points was 0.0015x10-6 kg/l, 0.0051x10-6 kg/l, and 0.0053x10-6 kg/l. Concentrations of Zn(zinc) was found to be 0.0310x10-6 kg/l, 0.028x10-6 kg/l, and 0.0337x10-6 kg/l. which the electrical conductivity was 192,33x10-4 mho/m, 197,23x10-4 mho/m, and 199,9x10-4 mho/m. Otherwise the average density of the river water was 1166.7x10-3 kg/m3, 1200x10-3 kg/m3, and 1233.3x10-3 kg/m3, respectively for point 1, 2, and 3.